Evaluating the Impact of Urban Competitive Advantages on Economic Revitalization of Deprived Inner Cities Through a Case Study Held in İstanbul - Yalçıntaş Ağan, Hande; Arkon, Cemal (Izmir Institute of Technology, 2008)
This dissertation assesses the impact of Urban Competitive Advantages in deprived inner city areas in Turkey and strength of the potential for marketability of those advantages, for economic revitalization in the case of Turkey. .The Urban Competitive Advantages Approach., compliant with latest discussions on urban economic regeneration, is a strong economy-based approach focusing on the need for recognition of inherent advantages of distressed inner cities and relies on the development of specific marketing mechanisms to promote those advantages in order to stimulate private inward investment. Accepting true contribution of the approach to urban regeneration, the thesis first examines several projects from abroad to determine key indicators in assessing the competitive capacity of a locality and then, makes use of those indicators in a case study in Istanbul in order to illustrate to what extent the present advantages contribute to stimulation of reinvestment in inner cities given the political uncertainties, economic instability, available financial mechanisms together with legislative and institutional capacities in Turkey. Finally, it is observed that resulting remarks on case study analyses support the main hypothesis of the thesis that .national policy directions and current regulatory, organizational and financial framework for urban regeneration in Turkey can only help finding best economic use of distressed inner city spaces when reformulated in the way they market competitive advantages of concerned spaces.. The dissertation concludes by recommending innovations and reviews through policy directions and necessary mechanisms in legislative, organizational and financial issues for Turkey.
Thesis (Doctoral)--Izmir Institute of Technology, City and Regional Planning, Izmir, 2008
Includes bibliographical references (leaves: 279-289)
Text in English; Abstract: Turkish and English
xviii, 291 leaves
Keywords: HT178.T82 Y16 2008; Urban renewal--Turkey--Istanbul; Inner cities--Economic aspects